Association of learning environment and self-directed learning ability among nursing undergraduates: a cross-sectional study using canonical correlation analysis. Issue 8 (29th August 2022) - Tang, Li-Qing; Zhu, Li-Jun; Wen, Li-Ying; Wang, An-Shi; Jin, Yue-Long; Chang, Wei-Wei
Abstract : Objectives: This study explores the relationship between the perception of the learning environment and self-directed learning (SDL) ability among nursing undergraduates. Design, setting and participants: A cross-sectional study was conducted in December 2020 with 1096 junior and senior undergraduate nursing students (aged 16–22) from Wannan Medical College in Anhui Province, China. Outcome measures: The Chinese version of the Dundee Ready Educational Environment Measure questionnaire and a validated Chinese version of college students' SDL ability scale were used to assess students' perceptions about their learning environment and their SDL ability. Canonical correlation analysis was performed to evaluate their correlation. Results: The total score for the learning environment was 120.60 (scoring rate: 60.30%), and the score for SDL ability was 89.25 (scoring rate: 63.75%). Analysis indicated that the first canonical correlation coefficient was 0.701 and the contribution rate was 94.26%. The perception of the learning environment was mainly determined by students' perception of learning (SPL) and academic self-perceptions (SASP), with SDL ability mainly determined by self-management ability and cooperative learning ability. SPL and SASP were positively correlated with self-management ability and cooperative learning ability. Multiple linear regression analysis revealed that SPL, SASP, students' perceptions of atmosphere and students' social self-perceptions had a significant impact on SDL ability. Conclusions: The SDL ability of nursing undergraduates was not high. SPL and SASP were positively correlated with self-management ability and cooperative learning ability. Nursing educators can improve students' SDL ability by changing their learning environment, using, for example, new student-centred teaching methods.